Fabrication of calixarene-based graphene-modified screen-printed carbon electrodes for selective detection of anthracene - Zainal, Putri Nur Syafieqah (2021)
Anthracene is one of the most widespread polycyclic aromatic hydrocarbons (PAHs) that consists of three fused benzene rings. To date, numerous approaches have been reported for electrochemical detection of anthracene based on various materials. Nevertheless, the critical issues in designing electrochemical sensors are the strategy to enhance the selectivity, sensitivity, and stability of the detection in environmental samples. Therefore, in this research work, different calix[4]arene-based materials such as tert-butylcalix[ 4]arene (C4), thiolated-calix[4]arene (TC4) and, calix[4]arene-based metalorganic framework (C4TCA@MOF) were used as a receptor and incorporated with coupling materials, which are electrochemically reduced graphene oxide (ERGO) and gold nanoparticles (AuNPs) to develop different strategies of electrochemical sensor for the determination of anthracene. In brief, the first sensor was constructed based on C4 deposited on ERGO/SPCE (C4/ERGOSPCE). The next sensor was proposed with a coupling material, AuNPs that was prepared through the synthetic route of Turkevich-Frens method and functionalized with TC4 to form TC4/AuNPs/ERGO-SPCE. Next, the third sensor was constructed by synthesizing a C4TCA@MOF through solvothermal method as a new receptor and deposited on AuNPs/ERGO (C4TCA@MOF/AuNPs/ERGO-SPCE). Under the optimal conditions, the C4/ERGO-SPCE exhibited a good linearity towards anthracene with concentration range from 2-8 μM and limit of detection (LOD) 0.02637 μM, while the performance of TC4/AuNPs/ERGO-SPCE increase comprehensively due to the presence of AuNPs with a linear concentration range from 1-7 μM and LOD 0.00649 μM. After the modification of C4 into C4TCA@MOF, the proposed sensor (C4TCA@MOF/AuNPs/ERGO-SPCE) revealed highest sensitivity and selectivity and demonstrated wide linear concentration range from 0.01-30 μM with LOD 0.00521 μM. The proposed sensor also was tested towards anthracene using portable potentiostat that was able to demonstrate a satisfactory recoveries (90-93%) and statistical analysis of relative error (2.27- 4.60%). With these proven advantages, the proposed sensors have a huge potential as an alternative analysis of anthracene in near future.